Bimbingan Konseling Islam: Sebagai Metode Dalam Meminimalisir Perilaku Menyimpang Pada Siswa di Madrasah Aliyah Darud Da’wah Wal Irsyad (DDI) Alliritangae Kabupaten Maros - Muhammad Sabiq Al-Khair; Alang, Sattu; Hamid, Ilham (Al-Irsyad Al-Nafs : Jurnal Bimbingan dan Penyuluhan Islam, 2024)
This research raises the main problem of "Islamic Counseling Guidance Methods in Minimizing Deviant Behavior in Students at Madrasah Aliyah Darud Da'wah Wal Irsyad (DDI) Alliritengae Maros Regency" with sub-problems consisting of 1. How Islamic Counseling Guidance attempts to minimize deviant behavior among students at Madrasah Aliyah Darud Da'wah Wal Irsyad (DDI) Alliritengae, Maros Regency? 2. What are the results of Islamic Counseling Guidance's efforts to minimize deviant behavior among students at Madrasah Aliyah Darud Da'wah Wal Irsyad (DDI) Alliritengae, Maros Regency? This research is a descriptive qualitative research type located at Madrasah Aliyah Darud Da'wah Wal Irsyad (DDI) Alliritengae, Maros Regency, using a guidance approach. The data sources contained in this research consist of primary and secondary data sources, where the primary data source is the Guidance Counseling teacher as the key informant, while the additional informants in the primary data source are the Madrasah head, several homeroom teachers and several students. Meanwhile, books, journals, articles, websites and other complementary data sources are secondary data sources. The method for collecting data from research is using observation, interviews and documentation methods. The research instrument is the researcher himself. Then data analysis was carried out in three stages, namely data reduction, data presentation and drawing conclusions. The results of this research show that the efforts of Islamic Counseling Guidance in minimizing deviant behavior among students at Madrasah Aliyah Darud Da'wah Wal Irsyad (DDI) Alliritengae Maros Regency are 1. Provide warnings/reprimands to students, 2. Mediate and approach students, 3. Personal counseling guidance, 4. Group counseling guidance, 5. Provide educational sanctions and 6. Supervision and cooperation with students' parents. The results of Islamic Counseling Guidance's efforts to minimize deviant behavior among students at Madrasah Aliyah Darud Da'wah Wal Irsyad (DDI) Alliritengae Maros Regency are 1. Students show good morals by not committing deviant behavior anymore, 2. Students are able to realize their mistakes. they do and want to change to be better than before and 3. Students' learning percentage and religious moral values ​​have increased.